SAT0081 Seropositivity is Associated with Increased Arterial Stiffness in Rheumatoid Arthritis Patients: Results from the Norfolk Arthritis Register. (23rd January 2014) - Skeoch, S.; Verstappen, S.; Chipping, J.; Marshall, T.; Symmons, D.; Bruce, I.
Abstract : Background: Patients with rheumatoid arthritis (RA) have a 50% increased risk of cardiovascular disease (CVD) not fully explained by traditional risk factors. Arterial stiffness is an independent predictor of CVD and can be measured non-invasively using mobile, operator independent devices. RA patients have been found to have increased arterial stiffness compared to controls and improvements have been demonstrated, following anti-TNF therapy. Objectives: The aim of the current study is to investigate the relationship between arterial stiffness and disease characteristics in a cohort of patients with established inflammatory polyarthritis (IP). Methods: Arterial stiffness was measured in a subset of patients in the Norfolk Arthritis Register (a primary inception cohort of patients with adult onset IP), at 15 year follow up. The stiffness index (SI), an indirect measure of arterial stiffness, was measured using an automated digital photoplethysmography device (Pulse Trace PCA2, Micromedical). Concurrent clinical assessment was performed, including disease activity 28 score (DAS-28 score) and blood was taken for CRP measurement and serological status with seropositivity being defined as being positive for rheumatoid factor and/or anti-citrullinated protein antibody positive (ACPA). The patient completed a health assessment questionnaire (HAQ). Non-parametric tests were used to test correlation of SI with IP disease characteristics and traditional CVD risk factors. Results: Arterial stiffness was measured in 33 subjects. Median (IQR) age was 61.0(44.9, 71.9) years and 23(69.7%) were female. 28(84.8%) of subjects were seropositive. Median DAS-28 score was 3.23(2.41, 3.34), HAQ score was 1.00(0.25, 1.5) and CRP was 8.71(6.8, 18.8)mg/dl. The proportion of patients with a history of clinical CVD, hypertension and diabetes was 12.1%, 36.4% and 9.1% respectively. The median (IQR) SI was 10.05(8.98, 10.79) m/s. SI was significantly higher in subjects who were seropositive (p=0.02) and there was a trend towards a correlation between SI and CRP (rho=0.36, p=0.08). There was no significant association with traditional CVD risk factors or prior history of clinical cardiovascular events. Conclusions: In this small exploratory study, seropositive patients had increased arterial stiffness. This finding is in agreement with previously observed increased risk of clinical CVD in these patients. The low number of clinical cardiovascular events in the cohort may explain the lack of association of SI with history of CVD in this study. Digital photoplethysmography could provide an effective, non-invasive tool with which to investigate and monitor cardiovascular risk in RA. Disclosure of Interest: None Declared